Modeling the spatial distribution of Culicoides species (Diptera: Ceratopogonidae) as vectors of animal diseases in Ethiopia - Eyerusalem Fetene; Getachew Teka; Hana Dejene; Deresegn Mandefro; Tsedale Teshome; Dawit Temesgen; Haileleul Negussie; Tesfaye Mulatu; Megarsa Bedasa Jaleta; Samson Leta (Scientific Reports, 2022)
Abstract Culicoides biting midges (Diptera: Ceratopogonidae) are the major vectors of bluetongue, Schmallenberg, and African horse sickness viruses. This study was conducted to survey Culicoides species in different parts of Ethiopia and to develop habitat suitability for the major Culicoides species in Ethiopia. Culicoides traps were set in different parts of the country from December 2018 to April 2021 using UV light Onderstepoort traps and the collected Culicoides were sorted to species level. To develop the species distribution model for the two predominant Culicoides species, namely Culicoides imicola and C. kingi, an ensemble modeling technique was used with the Biomod2 package of R software. KAPPA True skill statistics (TSS) and ROC curve were used to evaluate the accuracy of species distribution models. In the ensemble modeling, models which score TSS values greater than 0.8 were considered. Negative binomialregression models were used to evaluate the relationship between C. imicola and C. kingi catch and various environmental and climatic factors. During the study period, a total of 9148 Culicoides were collected from 66 trapping sites. Of the total 9148, 8576 of them belongs to seven species and the remaining 572 Culicoides were unidentified. The predominant species was C. imicola (52.8%), followed by C. kingi (23.6%). The abundance of these two species was highly influenced by the agro-ecological zone of the capture sites and the proximity of the capture sites to livestock farms. Climatic variables such as mean annual minimum and maximum temperature and mean annual rainfall were found to influence the catch of C. imicola at the different study sites. The ensemble model performed very well for both species with KAPPA (0.9), TSS (0.98), and ROC (0.999) for C. imicola and KAPPA (0.889), TSS (0.999), and ROC (0.999) for C. kingi. Culicoides imicola has a larger suitability range compared to C. kingi. The Great Rift Valley in Ethiopia, the southern and eastern parts of the country, and the areas along the Blue Nile and Lake Tana basins in northern Ethiopia were particularly suitable for C. imicola. High suitability for C. kingi was found in central Ethiopia and the Southern Nations, Nationalities and Peoples Region (SNNPR). The habitat suitability model developed here could help researchers better understand where the above vector-borne diseases are likely to occur and target surveillance to high-risk areas.